Rapid identification of bacteria using a multiplex polymerase chain reaction system for acute abdominal infections - Kakizaki, Nanako; Asai, Koji; Kuroda, Makoto; Watanabe, Ryutaro; Kujiraoka, Manabu; Sekizuka, Tsuyoshi; Katagiri, Miwa; Moriyama, Hodaka; Watanabe, Manabu; Saida, Yoshihisa (Frontiers in Microbiology, 2023)
Purpose: Acute abdominal infections can be fatal if the causative organism (s) are misidentified. The spread of antimicrobial-resistant bacteria has become a serious problem worldwide, making antibiotic selection extremely difficult. Using quantitative metagenomic analysis, we evaluated a commercial multiplex polymerase chain reaction (PCR) system (FilmArray™, bioMérieux, Marcy-l'Étoile, France) for the rapid identification of causative bacteria. Methods: The cases of ten patients with acute abdominal infections were enrolled in this retrospective study. There were six cases of perforated peritonitis and four cases of intraabdominal abscess. Fluid collected from the acute surgical abdominal infections were examined. Results: All specimens tested positive for microorganisms in culture, and six involved two or more microorganisms. Using the multiplex PCR system, nine of ten specimens were found to involve at least one microorganism. One specimen was not included in the multiplex PCR system panel. Nineteen of 21 microorganisms (90.5%) isolated by culture were detected by the multiplex PCR system. Microorganisms with very small numbers of reads (19 reads) were detectable. Conclusions: This multiplex PCR system showed a high detection rate for causative microorganisms in ascites and intraabdominal abscesses. This system may be suitable as an affordable rapid identification system for causative bacteria in these cases.